Dukungan Sosial Suami Terhadap Istri untuk Menggunakan Alat Kontrasepsi Medis Operasi Wanita (MOW) (Studi Kualitatif pada Pasangan Usia Subur Unmet Need di Kecamatan Puger Kabupaten Jember) Husband's Social Support on Their Wive to Use Contraception “Meto - Ismi Dita Muniroh; Novia Luthviatin; Erdi Istiaji (Pustaka Kesehatan, 2014)
Family planning program is an effort to solve the demoghraphy issue in Indonesia.Metode Operasi Wanita (MOW) is a contraception method that can be exact choice for family who want to stop having children and end the pregnancy. Husband’s social support is needed for MOW as a contraception method of family planning program,especially for unmet need Of eligible couples. In 2012, Puger sub district had the highest of eligible couples of unmet need in Jember regency.The objective of this research is to explain husband’s social support for wive to use contraception of MOW. This research applied qualitative-method.The data was collected by in-depth interviews.The informants were defined by purposive sampling. Based on the results of indepth interview, it was known that most of husband didn’t give social support in three aspects. It was caused most of them had a poor knowledge about MOW and high cost that have to be paid as administrative and accomodative cost for MOW services. There were some factors caused unmet needs in Puger Sub district : (1) they are officer of family planning program and society still had limited knowledge about MOW; (2) husbands forbade their wives to use MOW; (3) it’s caused cost must be paid. It’s expected to State Ministry for Population/ National Family Planning Coordinating Board in Jember to socialize MOW communicatively and comprehensively, continuously.   Keywords: Husband’s Social support, Metode Operasi Wanita (MOW), Unmet Need